Comparison of Surface Microhardness of Portland Cement Associated with Niobium Oxide and Zirconium Nanoparticles with the Mineral Aggregate Trioxide - Pinedo Saldaña, Angel Eduardo (2026)
To determine the surface microhardness of white portland cement associated with niobium nanoparticles, white portland cement associated with zirconium nanoparticles, and mineral trioxide aggregate. The present study is an experimental in-vitro study. The sample consisted of 03 study groups. These were divided into 09 subgroups of 04 hours, 14 days and 28 days. The instrument used to record the surface mechanical microhardness was the Vickers microdurometer. The Shapiro-Wilk statistical analysis was then performed to identify the normality of the data. The Anova test was applied to compare between the three groups and then the Tukey test for multiple comparisons with a 95% confidence level. White Portland cement associated with zirconium nanoparticles had the highest hardness value (p<0.05), followed by white Portland cement associated with niobium nanoparticles and aggregate control cement of mineral trioxide. The lowest value of surface microhardness was obtained by the addition of mineral trioxide (p<0.05). Surface microhardness values were significantly higher at 28 days than at 04 hours for all groups evaluated. White Portland cement with/without nanoparticulate additives generated higher surface microhardness than the control group added mineral trioxide in the evaluation periods.